MOBILISASI DINI UNTUK PENYEMBUHAN LUKA POST OPERASI SECTIO CAESAERA (STUDI LITERATUR) - Yuli Suryanti; Vera Yuanita; Fyzria Qudratullah; Sri Emilda (Jurnal Kesehatan dan Pembangunan, 2024)
Early mobilization is very useful in the wound healing process, mobilization is needed to increase self-reliance to improve health, slow down the disease process, especially degenerative diseases and for actualization. This study aims to determine the early mobilization of mothers postoperative Sectio Caesarea. The research method uses a systematic review. Selection of articles through the Google Scholar database, EBSCO, Proquest, Oxford with journal criteria related to early mobilization of mothers after Sectio Caesarea surgery, which have been published, journals published from 2015 to 2020. The results of a study of 10 journals showed that Sectio Caesarea wound healing was affected by early mobilization. Early mobilization carried out in post-Sectio Caesarea mothers can speed up the wound healing process of Sectio Caesarea surgery. Early mobilization starts from light exercise in bed until being able to get out of bed, walk to the bathroom and walk out of the room. Early mobilization is very beneficial in the wound healing process, one of which is preventing the potential for thrombosis and thromboembolism, the potential for decreased functional ability, infection and so on.